Hydranencephaly- a rare case of neglected child with enlarging head size - Dr. Shefali Patel; B Sandeep; B Kiran (Pediatric Review: International Journal of Pediatric Research, 2022)
Hydranencephaly is a rare congenital abnormality characterized by the absence and replacement ofthe cerebral hemisphere by cerebrospinal fluid. Here we report a rare case of a child who presentedvery late at 2 years of age with a massively enlarged head size with spasticity of all four limbs,suspected of hydrocephalous at first while on further work up diagnosed to have hydranencephaly.This report is aimed to make clinicians aware of a rare condition which can present very late even upto 2 years of age.